2007
DOI: 10.1188/07.onf.e51-e59
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of a Cognitive-Behavioral Intervention for Insomnia in Breast Cancer Survivors

Abstract: Breast cancer survivors can benefit from a cognitive-behavioral intervention for chronic insomnia. Sleep education and hygiene, a less complex treatment than a multicomponent intervention, also is effective in treating insomnia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
112
1
5

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(121 citation statements)
references
References 42 publications
3
112
1
5
Order By: Relevance
“…They reported difficulty sleeping and that a lack of exercise, dietary problems, and air pollution contributed to their breast cancer. All of these observations are supported by numerous studies (Stewart et al, 2001;Anderson et al, 2003;Carpenter et al, 2004;Dirksen & Epstein, 2007;Wang et al ., 2010;Ferrucci et al, 2011;Panjari et al, 2011). Causal attributions may impact cancer survivors' quality of life (Stewart et al, 2001;Ferrucci et al, 2011).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…They reported difficulty sleeping and that a lack of exercise, dietary problems, and air pollution contributed to their breast cancer. All of these observations are supported by numerous studies (Stewart et al, 2001;Anderson et al, 2003;Carpenter et al, 2004;Dirksen & Epstein, 2007;Wang et al ., 2010;Ferrucci et al, 2011;Panjari et al, 2011). Causal attributions may impact cancer survivors' quality of life (Stewart et al, 2001;Ferrucci et al, 2011).…”
Section: Discussionsupporting
confidence: 76%
“…Cancer patients frequently experience insomnia. Cancer patients generally have difficulty sleeping (Epstein & Dirksen, 2007). Between 30% and 73% of cancer patients experience difficulty sleeping (Anderson et al, 2003).…”
Section: Relationships Between Cause Of Cancer and Breast Cancerrelatmentioning
confidence: 99%
See 1 more Smart Citation
“…Sleep hygiene recommendations include caffeine and exercise avoidance near bedtime, comfortable sleep surroundings (dark, cool, peaceful, and relaxing), and soothing activities at bedtime (reading, tranquil music). Several studies have demonstrated the benefit of behavioral therapies for sleep improvement and fatigue in long-term cancer survivors [31][32][33] . In addition, behavioral therapies may often be combined with complimentary therapies to address sleep issues.…”
Section: Sleep Therapymentioning
confidence: 99%
“…CBT-I has welldocumented benefits, including improvements in insomnia, sleep continuity, and daytime symptoms among patients with a number of comorbid medical conditions. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] CBT-I also may improve sleep for HF patients who dislike the adverse effects of hypnotic medications 12 and are at especially high risk for insomnia and disabling daytime symptoms 34 that are often attributed to HF itself. However, the effects of CBT-I in HF patient have not been examined, and it is not clear that the results of previous studies of CBT-I in people with other chronic medical conditions are generalizable to the HF population.…”
mentioning
confidence: 99%